Fungal Meningoencephalitis Masquerading as Metabolic Encephalopathy: A Case Report in a 65-Year-Old Geriatric Patient - Kurniawati, Nita; Erwin, Ferdinand (AKSONA, 2025)
Highlight: A geriatric patient may present with subtle or nonspecific symptoms of meningoencephalitis, such as confusion, altered mental status, or lethargy, rather than classic signs like fever and neck stiffness. Negative CSF cultures of fungal infection should not delay the initiation of antifungal therapy.   ABSTRACT Introduction: Infectious pathogens or autoimmune disorders can cause meningoencephalitis. Symptoms include headache, fever, altered mental status, seizure, or neurological deficits. Symptoms frequently manifest atypically in the elderly, which can result in delayed treatment. This case emphasizes how important it is to consider meningoencephalitis in elderly patients with altered consciousness, even without typical signs of it. Case: A 65-year-old female with a history of recurrent hyponatremia and hypokalemia arrived at the emergency room with sudden loss of consciousness, vomiting, and behavioral changes that persisted for a week. The neurological examination and brain CT scan revealed no abnormalities. Severe electrolyte imbalances prompted the initial diagnosis of metabolic encephalopathy. Following progressive electrolyte correction, the patient’s mental condition improved. On the second day, she had generalized seizures and developed right-sided hemiparesis. An MRI of the head with contrast showed thicker dura mater and leptomeningeal enhancement in both hemispheres, indicating meningoencephalitis. Ceftriaxone and dexamethasone were administered intravenously, along with levetiracetam, to treat seizures. The next day, cerebrospinal fluid analysis showed Candida spores, but cultures were negative. Intravenous fluconazole was then added to the therapy. Throughout her two-week stay, the patient’s neurological condition improved consistently. Conclusion:Fungal causes should be considered in cases with unclear meningoencephalitis in the elderly, even if fever or meningeal signs are not present. Although CSF culture continues to be the gold standard for diagnosing fungal CNS infection, negative results should not delay the start of antifungal therapy. Early initiation of targeted antimicrobial therapy is crucial for successful results in these cases.